Tunable domain wall pinning behavior by notch geometry in CoFeB nanostrip under nano-pulse current injection (Kuwait Journal of Science)
To optimally control the domain wall (DW) pinning behavior in the ferromagnetic nanostrip, some focus is on utilizing a geometrical notch as an artificial pinning potential. Most of the studies were intended to explain the dynamics of DW structure when it passes or moves out from the notch. However, there is still a lack of discussion about the effect of the geometrical structure of notches in the nanostrips. This work investigated the effect of notch geometry on the domain wall tunability pinning behavior under nanosecond pulse current injection using micromagnetic simulation from its initial ground-state condition. The micromagnetic model of the material mimicked the perpendicular magnetization of the CoFeB stripe-shaped nanowire with a perfect single crystalline structure. The DW depinning condition determined by the edge of DW leaves out the notch area, which was related to the minimum energy needed to surpass the artificial pinning potential in the nanostrip made by the notch. The micromagnetic results showed that the notch depth variation linearly increased the depinning current density value. Moreover, the depinning current value was significantly increasing on the smaller nanostrip slit analog to the larger notch depth above 20 nm. In this case, the medium size of nanostrip geometries and notch sizes are considerable for the effective DW pinning and control in the CoFeB nanostrip. © 2025 The Authors